Conspicuous Consumption of Luxury Goods in the Kingdom of Saudi Arabia: Applied Study on Jeddah City - Bokhari, Abla Abdul-Hameed; Aljuhani, Safa Hamed (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to analyze the conspicuous consumption of luxury goods in Kingdom of Saudi Arabia. To achieve this, the descriptive analytical and econometric approach was employed to describe the phenomenon, and review the theoretical and applied literature, to come out with the most important motivations of this type of consumption. In addition, a questionnaire was distributed to 712 individuals in Jeddah city. Through analyzing and estimating the consumption function to measure the effect of disposable personal income, alongside: gender, marital status, age, educational level, and employment status, on the consumption of luxury goods. The results indicated that the disposable personal income is a major determinant of luxury goods consumption. The marginal propensity to consume was estimated at 0.045, while the elasticity of income demand is 0.431, indicating that luxury goods are considered as necessary for Saudi consumer. The study concluded that economic rationalization requires more social awareness to distinguish between what is necessary and luxury, and between productive consumption and conspicuous unrationed consumption. Consequently, the study recommended the necessity of raising the level of awareness of the need to rationalize consumption and the importance of saving and investment. This in addition to the importance of developing an approved classification for the consumption’s items. It is also important to provide detailed statistical data, to support and stimulate in-depth research in the areas of household consumption expenditure and its ordinary and conspicuous patterns, so as to guide reform policies that effectively contribute to achieving the country’s aspirations and long-term strategies.
Keywords: luxury goods; consumption patterns; apparent consumption; rational consumption